BERAIM PANGLIMA KASU BARAT, ROMAN SEJARAH KARYA BM SYAMSUDDIN: SUATU KAJIAN SOSIAL KEMELAYUAN - Syam, Efrizal Amarullah (Jurnal Ilmu Budaya, 2013)
The analysis deals with the social condition of Malay society which is reflected in a historical romance entitles Beraim Panglima Kasu Barat. This romace shows the life of the archipelagic Malay who keeps their tradition, norms, prohition, and islamic doctrines. This analysis describes the historic battle, social values, emotion and social norms attached in archipelagic Malay. Hopefully, this description will increase the horizon about Malay society and in the same time it can encourage the Malay identity and spirit.